Ranking open source application integration frameworks based on maintainability metrics: A review of five‐year evolution. (16th July 2019) - Frantz, Rafael Z.; Rehbein, Matheus H.; Berlezi, Rodolfo; Roos‐Frantz, Fabricia
Summary: Integration frameworks are specialized software tools built and adapted to facilitate the design and implementation of integration solutions. An integration solution allows for the reuse of applications from the software ecosystem of companies to support their business processes. There are several open‐source integration frameworks available on the market designed to operate in a business context to manipulate structured data; however, increasingly, they are required to deal with unstructured and large volumes of data, thus requiring effort to adapt these frameworks to work with unstructured and large volume of data. Choosing the framework, which is the easiest to be adapted, is not a trivial task. In this article, we review the newest stable versions of four open‐source integration frameworks by analyzing how they have evolved regarding their adaptive maintainability over five years. We rank them according to their maintainability degree and compare past and current versions of each framework. To encourage and enable researchers and developers to replicate our experiments, with the aim of verifying our findings, and to experiment with new versions of the integration frameworks analyzed, we detail the experimental protocol used while also having made all the required software involved available on the Web.